Economic viability of scaling improved bean technologies in Burundi and Zimbabwe - Ochieng, Justus; Maina, Joel; White, Doug; Rubyogo, Jean Claude; Nduwarugira, Eric; Birachi, Eliud; Chepchirchir, Ruth; Katungi, Enid; Nchanji, Eileen; Kalemera, Sylvia; Mutua, Mercy; Chiwawa, Andrew; et al. (Wiley, 2025)
Scaling improved bean varieties and complementary technologies are important to improve crop productivity incomes and food and nutrition security in Sub‐Saharan Africa. In Burundi and Zimbabwe, bean technologies were promoted through a demand‐led and public–private partnership model. While econometric approaches have been used to estimate the impact of enhanced technologies on farmers' livelihoods for a long time, no economic feasibility analysis has been done. Most analyses focus on farmers livelihoods, overlooking other value chain actors like traders, processors, and seed producers including community seed multipliers. Thus, this study contributes to the literature by conducting an economic feasibility analysis that includes all actors in the bean value chain and estimates additional investments attracted from public and private stakeholders. We further identified gains or losses on account of the externalities generated through different value chain actors. We find positive net present values (NPV) and a benefit–cost ratio (BCR) greater than one. This implies that the economic benefits of the bean value chain improvement program in the two countries are larger than their costs. Farmers and traders are the main beneficiaries, receiving 99% and 65% of the net economic benefits generated in the bean value chain in Burundi and Zimbabwe, respectively. Finally, we find the intervention sustainable and resilient against economic shocks, making it worth replicating in other countries in sub‐Sahara Africa and beyond. Pragmatic and policy options are recommended to inform future interventions of a similar nature.